Simultaneous targeting therapy for lung metastasis and breast tumor by blocking the NF-κB signaling pathway using Celastrol-loaded micelles - Yue Zhao; Yanan Tan; Tingting Meng; Xuan Liu; Yun Zhu; Yun Hong; Xiqin Yang; Hong Yuan; Xuan Huang; Fuqiang Hu (Taylor & Francis Group, 2018)
Metastasis is one of the major obstacles for successful therapy of breast tumor. To inhibit the metastasis and growth of breast tumor simultaneously, a Celastrol (Cela) loaded glucolipid-like conjugates (CSOSA/Cela) with αvβ3-ligand Tetraiodothyroacetic acid (TET) modification (TET-CSOSA/Cela) were established to block nuclear factor-kappa B (NF-κB) signaling pathway. The distribution of TET-CSOSA was remarkably increased in lung metastasis and primary tumor of 4T1 tumor-bearing mice by means of αvβ3 receptor-mediated interaction. The results demonstrated that TET-CSOSA/Cela significantly suppressed Bcl-2 activation of lung metastatic cells and reduced MMP-9 expression of 4T1 breast tumor cells by blocking NF-κB. The inhibitory rates of TET-CSOSA/Cela against lung metastasis and primary tumor were raised to 90.72 and 81.15%, compared to those of Celastrol (72.15 and 46.40%), respectively. All results demonstrated the αvβ3 receptor targeted TET-CSOSA/Cela micelles exhibited great potential in treating lung metastasis and primary tumor simultaneously via blocking NF-κB signaling pathway.